The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1891/0730-0832.20.8.15
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Very Preterm Neonates as Documented Using NIDCAP Observations

Abstract: The most frequently observed behaviors were irregular respirations, pink color, postured flexion of the extremities, immature light sleep, and drowsiness. Least frequently observed behaviors consisted of burps, bowel movement, grunting, smooth motor movements, cooing, and speech movement. Regression analysis illustrated that the pattern of behavior was significantly similar week to week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
0
13
0
5
Order By: Relevance
“…However, these investigators did not specify the procedures that they observed. 26 The most important finding of this study was that we found a subset of 8 NIDCAP movements that seem to be associated with acute pain in preterm infants. Although some of the 8 NIDCAP movements that we identified are included in other pain measures, others have not been described as behavioral pain cues before this study.…”
Section: Discussionmentioning
confidence: 64%
“…However, these investigators did not specify the procedures that they observed. 26 The most important finding of this study was that we found a subset of 8 NIDCAP movements that seem to be associated with acute pain in preterm infants. Although some of the 8 NIDCAP movements that we identified are included in other pain measures, others have not been described as behavioral pain cues before this study.…”
Section: Discussionmentioning
confidence: 64%
“…Studies using the NIDCAPÒ to evaluate the effects of routine care giving in the NICU are not only few in number, but have pooled all handling to make general comments regarding the infants' responses, 14 have not included the full range of NIDCAPÒ behaviors, 19 have not specified the procedures observed in the study, 20 or have not included diaper changing as one of the procedures being evaluated. 13,15 Thus, the aims of this study are the following: 1.…”
mentioning
confidence: 99%
“…No differences were found in stress behaviors related to the respiratorycirculatory system and the digestive system. Regulation of the respiratory-circulatory system tends to be observed at the gestational age of 24-30 weeks in premature infants 10) , and physiological stress decreases over time until it stabilizes at 32 weeks 11) . As participants in this study were at term age at the time of the NIDCAP behavioral observations, respiratory-circulatory system stresses were expected to have stabilized.…”
Section: Discussionmentioning
confidence: 99%
“…Stress signs of the motor system are also easily observed in premature infants at the gestational age of 24-30 weeks. Pressler et al and Grunau et al suggested that stress signs of the motor system arise from the organization of the n e u r o b e h a v i o r a l s y s t e m a c c o m p a n i e d b y g e s t a t i o n a l a g e ( m a t u r i t y ) , d i s e a s e , a n d environmental factors 10,12) . Grunau et al also…”
Section: Discussionmentioning
confidence: 99%